Plan de negocios para implementar una empresa productora y comercializadora de infusiones de frutas exóticas - Mediavilla Vaca, Ana Inés (2010)
In Equator a great diversity of medicinal and aromatic plants exists (El Hoy, 2006). Considering this extensive biodiversity, and the high fruit-bearing and aromatic infusions consumption tendencies and tea inside the country this be planted project to determine the viability of carry out the production and commercialization of aromatic herbal teas with flavors to exotic fruits in the city of Quito. With this purpose proceeded to analyze the macro environment, meso environment and the micro environment of the business. This analysis is described in chapter II. In chapter III a market research was carried out that allowed to collect information on the preferences of the consumers, data of the market and a detail of the necessary processes to carry out the production and the commercialization. The organizational structure, objective, politics and strategies; and, in general the basic aspects of the business are found explained in chapter IV. In chapter V the marketing plan was determined. In this chapter were presented the strategies that permit reach the objectives and goals of the business. The financial evaluation was analyzed in chapter VI. This chapter was of vital importance since it determined the levels of profit value of the business. In chapter VII the contingencies plan was established. Inside this plan some supposed were considered that affected directly the development of the business; and, at the same time were presented solutions that permit take decisions in unstable moments for the business. Finally, in the chapter VIII were established the conclusions and recommendations required by the business.